Application of metasurfaces in the design of performance-enhanced low-profile antennas - Park, Ikmo (EPJ Applied Metamaterials, 2018)
This paper presents a review of metasurface-based antennas conducted at the Microwave Communication Laboratory (MCL) of Ajou University in the Republic of Korea. In this paper, profile miniaturization, bandwidth enhancement, multiband operation, and radiation pattern control of metasurface-based antennas are considered. The paper first presents metasurface-based antennas implemented by placing various radiators on top of the metasurface. It then presents antennas implemented by placing the radiators below the metasurface with and without the ground plane. Metasurface-based antennas are not only able to achieve high efficiency with a low profile but they are also able to generate extra resonances from the metasurface structures, which significantly enhances the overall performance of the antennas. These additional resonances were utilized in multiband and/or wideband operations. In addition, the design of a planar compact wide-gain-bandwidth metasurface-based antenna and its radiation characteristics are presented at a terahertz (THz) frequency range. The THz antennas were designed with metasurfaces and a planar leaky-wave feeding structure. Finally, the outlook on future research at the MCL for antenna-related work and their applications using metasurfaces is provided.
Keywords: Array; Artificial magnetic conductors; Crossed dipoles; Metasurface; Sequential rotations; Wave resonances; Wide-band; Antenna; Array; Artificial magnetic conductor; Circular polarization; Crossed dipole/leaky-wave; Metamaterial; Metasurface; Sequential rotation; Surface wave resonance; Wideband